21st Century English Learning: a Revolution in Skills, Critical Thinking, Creativity, and Visual Communication - Budiyanto; Kabri, Kabri; Harapan, Edi; Purwanto, M Bambang (Asian Journal of Applied Education (AJAE), 2024)
Critical thinking and problem-solving, creativity and innovation, communication, and teamwork are some of these 21st-century abilities. It is possible to build these 21st century skills in any discipline. It is highly appropriate to study English as a subject in order to gain 21st century skills. To effectively and efficiently accomplish learning objectives, chemistry instructors must deliberately cultivate these 21st century competencies. Teachers can use scientific learning models, such as project-based, problem-based, discovery, or design-based learning models, to help students acquire the English language abilities they need for the twenty-first century. To help students gain 21st century abilities, these learning models must be applied as best as possible, adhering to the principles of the scientific method. The evaluation of 21st century abilities and the use of blended learning are also crucial.